PERANCANGAN SISTEM INFORMASI PEMESANAN CISSTIK RESEP EYANG BERBASIS WEBSITE - Randy Noufal Pradhitya, (2022)
Computers and the internet have also become an important part of our daily lives which really help to do work faster. Especially in the business world, the use of computers is very important. The use of computer technology will also be applied by Cisstik Recipes Eyang to record customers who want to order. Cisstik Recipe Eyang is a Micro, Small and Medium Enterprise (UMKM) in the culinary field that produces cheese stick snacks. In this Cisstik Eyang Recipe, all data collection still uses a notebook. By using this notebook, there will be a big risk or what we can call human error example, starting from an error in the number of Orders, losing order data and many other risks of loss. Cistik Recipes Eyang really needs to market its Products more broadly to get more customers. This marketing challenge is strategic to assist in serving Orders and Product marketing wider than Cistik Recipes Grandmother, how to Manage ordering data more easily and efficiently at Cistik Recipes Grandmother and how to design and create a food ordering application on the website-based Cistik Recipes Grandparents. How to implement the idea by designing a website using php and using MySql for the Database. So it is hoped that it can simplify and speed up customer, aiming as a solution to assist in serving Orders and marketing Products wider than Cistik Recipes Grandmother.